2021
DOI: 10.1017/s0954579421001577
|View full text |Cite
|
Sign up to set email alerts
|

Harshness and unpredictability: Childhood environmental links with immune and asthma outcomes

Abstract: The environment has pervasive impacts on human development, and two key environmental conditions – harshness and unpredictability – are proposed to be instrumental in tuning development. This study examined (1) how harsh and unpredictable environments related to immune and clinical outcomes in the context of childhood asthma, and (2) whether there were independent associations of harshness and unpredictability with these outcomes. Participants were 290 youth physician-diagnosed with asthma. Harshness was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…One study with clinical measures of immune outcomes found that unpredictability assessed as family structural changes does not predict asthma-relevant clinical or immune outcomes (Lam et al, 2022). At least one recent study examining indirect pathways between unpredictability from 0 to 5 years of age to body mass index (BMI) at 15 years, a predictor of adult metabolic syndrome and cardiovascular disease.…”
Section: Physical Healthmentioning
confidence: 99%
“…One study with clinical measures of immune outcomes found that unpredictability assessed as family structural changes does not predict asthma-relevant clinical or immune outcomes (Lam et al, 2022). At least one recent study examining indirect pathways between unpredictability from 0 to 5 years of age to body mass index (BMI) at 15 years, a predictor of adult metabolic syndrome and cardiovascular disease.…”
Section: Physical Healthmentioning
confidence: 99%
“…2 This association may be bidirectional: chronic FAinduced stress by itself may trigger Th2 immunity, as demonstrated in asthma. 5 Some portion of the cohort may have been mislabeled as having FA. Nevertheless, our study demonstrates that simply labeling, or even mislabeling, patients with FA may increase the rate of PDs.…”
Section: Food Allergy Is Associated With Increased Risk Of Developing...mentioning
confidence: 99%